ECTHR_COMMITTEE 34734/13 vom 8. Juni 2023 , AFFAIRE MAZOWIECKI c. POLOGNE - Ecthr Committee (2023)
Violation de l'article 8 - Droit au respect de la vie privée et familiale (Article 8-1 - Respect du domicile); Violation: 8;8-1